Hyers-Ulam Stability of Power Series Equations - M. Bidkham; H. A. Soleiman Mezerji; M. Eshaghi Gordji (Abstract and Applied Analysis)
We prove the Hyers-Ulam stability of power series equation ∑∞𝑛=0𝑎𝑛𝑥𝑛=0, where 𝑎𝑛 for 𝑛=0,1,2,3,… can be real or complex.